Influence Of Work-Life Balance, Compensation, And Work Environment On Nurses’ Job Satisfaction at Hj Hospital Anna Lasmanah Banjarnegara - Noni Indriyani; Purnadi Purnadi; Hermin Endratno; Arini Hidayah (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: To analyze the effect of work-life balance, compensation, and work environment on nurse job satisfaction at RSUD Hj. Anna Lasmanah Banjarnegara. Methodology: This quantitative study surveyed 133 nurses selected via purposive sampling. Data were analyzed using multiple linear regression. Results: Partially and simultaneously, work-life balance, compensation, and work environment have a positive and significant effect on job satisfaction. Findings: The work environment was identified as the most dominant factor influencing job satisfaction. Novelty: Providing recent empirical evidence regarding hospital human resource management at HJ. Anna Lasmanah Regional Hospital, Banjarnegara. Originality: This study offers a fresh perspective on healthcare job satisfaction factors within the public sector during the post-pandemic period. Conclusion: Optimizing the work environment and compensation systems is crucial to enhance nurse motivation and reduce turnover rates. Type of Paper: Empirical Research Paper.